Phenolphthalein-containing laxative use in relation to adenomatous colorectal polyps in three studies. - Longnecker, M P (1997)
Phenolphthalein, the active ingredient in many laxatives, was recently found to be a carcinogen in animal models. Human data suggest a laxative-colon cancer association, but few data specifically address the effects of phenolthalein-containing laxatives. We examined use of phenolphtalein-containing laxatives in relation to occurrence of adenomatous colorectal polyps in data from three case-control studies. The study conducted in Los Angeles, California (1991-1993), and the two studies conducted in North Carolina (1988-1990 and 1992-1995) altogether included 866 cases and 1,066 controls. The prevalence of using phenolphthalein-containing laxatives at least once a week in the recent past, however, was less than 5% among these subjects. The multivariate-adjusted odds ratios associated with recent use of phenolphthalein-containing laxatives once a week or more were 1.8 -95% confidence interval (CI), 0.5-6.2] in Los Angeles, 1.0 (CI, 0.4-2.2) in North Carolina (1988-1990), and 1.1 (CI, 0.2-5.7) in North Carolina (1992-1995). For use of other types of laxatives, the corresponding odds ratios were 1.3 (CI, 0.9-1.9) in Los Angeles, 1.0 (CI, 0.5-1.7) in North Carolina (1988-1990), and 0.9 (CI, 0.4-1.8) in North Carolina (1992-1995). Although the low prevalence of frequent use made for relatively wide confidence intervals, overall these data suggest that use of phenolphthalein-containing laxatives does not increase risk of adenomatous colorectal polyps.